Three dimensional printed nanostructure biomaterials for bone tissue engineering - Marew, Tesfa; Birhanu, Gebremariam (Regenerative therapy, 2021)
The suffering from organ dysfunction due to damaged or diseased tissue/bone has been globally on the rise. Current treatment strategies for non-union bone defects include: the use of autografts, allografts, synthetic grafts and free vascularized fibular grafts. Bone tissue engineering has emerged as an alternative for fracture repair to satisfy the current unmet need of bone grafts and to alleviate the problems associated with autografts and allografts. The technology offers the possibility to induce new functional bone regeneration using synergistic combination of functional biomaterials (scaffolds), cells, and growth factors. Bone scaffolds are typically made of porous biodegradable materials that provide the mechanical support during repair and regeneration of damaged or diseased bone. Significant progress has been made towards scaffold materials for structural support, desired osteogenesis and angiogenesis abilities. Thanks for innovative scaffolds fabrication technologies, bioresorbable scaffolds with controlled porosity and tailored properties are possible today. Despite the presence of different bone scaffold fabrication methods, pore size, shape and interconnectivity have not yet been fully controlled in most of the methods. Moreover, scaffolds with tailored porosity for specific defects are still difficult to manufacture. Nevertheless, such scaffolds can be designed and fabricated using three dimensional (3D) printing approaches. 3D printing technology, as an advanced tissue scaffold fabrication method, offers the opportunity to produce complex geometries with distinct advantages. The technology has been used for the production of various types of bodily constructs such as blood vessels, vascular networks, bones, cartilages, exoskeletons, eyeglasses, cell cultures, tissues, organs and novel drug delivery devices. This review focuses on 3D printed scaffolds and their application in bone repair and regeneration. In addition, different classes of biomaterials commonly employed for the fabrication of 3D nano scaffolds for bone tissue engineering application so far are briefly discussed. •Various 3D printed scaffolds used for bone tissue regeneration are discussed.•Different biomaterials commonly employed for fabrication of 3D scaffolds are discussed.•3D printing and its advantage over the other scaffolds is discussed.•Commonly used biomaterials for 3D printed scaffolds for bone regeneration are addressed.